2018
DOI: 10.1523/jneurosci.2154-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Positive and Negative Expectations on Human Pain Perception Engage Separate But Interrelated and Dependently Regulated Cerebral Mechanisms

Abstract: Expectations substantially influence pain perception, but the relationship between positive and negative expectations remains unclear. Recent evidence indicates that the integration between pain-related expectations and prediction errors is crucial for pain perception, which suggests that aversive prediction error-associated regions, such as the anterior insular cortex (aIC) and rostral anterior cingulate cortex (rACC), may play a pivotal role in expectation-induced pain modulation and help to delineate the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 75 publications
2
32
0
2
Order By: Relevance
“…These studies have demonstrated that social observation can also elicit expectancy effects on pain (Egorova et al, 2015;Tu et al, 2019a). In parallel, studies using fMRI have demonstrated the cue-based expectancy effects on painevoked brain responses (Koyama et al, 2005;Atlas et al, 2010;Jensen et al, 2015;Shih et al, 2019). Consistent with these studies, our results showed that cue-based expectation modulated both perceived intensity and neurobiological responses of pain ( Fig.…”
Section: Cue-based Expectancy Effects On Painsupporting
confidence: 89%
See 2 more Smart Citations
“…These studies have demonstrated that social observation can also elicit expectancy effects on pain (Egorova et al, 2015;Tu et al, 2019a). In parallel, studies using fMRI have demonstrated the cue-based expectancy effects on painevoked brain responses (Koyama et al, 2005;Atlas et al, 2010;Jensen et al, 2015;Shih et al, 2019). Consistent with these studies, our results showed that cue-based expectation modulated both perceived intensity and neurobiological responses of pain ( Fig.…”
Section: Cue-based Expectancy Effects On Painsupporting
confidence: 89%
“…These brain regions associated with cue-based expectancy effects on pain were largely overlapping with the neurological pain signature (Wager et al, 2013). To illustrate pain-evoked brain responses following different cues in the brain regions associated with cue-based effects on pain (Atlas et al, 2010;Jensen et al, 2015;Shih et al, 2019), dACC, SMA, bilateral insula, bilateral putamen, and bilateral thalamus were selected as ROIs. Pain-evoked brain responses in these ROIs were extracted and are shown in Figure 2E.…”
Section: Cue-based Expectancy Effects During Pain Experience and Antimentioning
confidence: 99%
See 1 more Smart Citation
“…Patient expectations can also significantly influence pain perception [40][41][42]. Cumulative evidence shows that subjects who have been primed to expect good pain relief subsequently exhibit decreased pain perception and associated cerebral activity in response to noxious stimulation -a phenomenon known as placebo analgesia [43][44][45][46][47].…”
Section: Cognitive Influences On Rebound Painmentioning
confidence: 99%
“…In particular, the limbic cortex appears to modulate nociceptive transmission via either the activation or the inhibition of PAG efferent connections to brainstem neurons that project to laminae I and V of the dorsal horn of the spinal cord (Butler and Finn, 2009 for review; Nathan, 1977; Ohara et al, 2005). Although PAG neurons also play an important role in pain expectation in humans (Fairhurst et al, 2007; Shih et al, 2019; Tracey et al, 2002) and receive inputs from hypothalamic neurons (Falconi-Sobrinho et al, 2017a; Ullah et al, 2017), it remains unknown whether the cortical modulation of nociception is mediated by hypothalamic projections to the PAG. In fact, the AH is part of the medial hypothalamus defensive system that is activated in animals exposed to a natural predator (Canteras, 2002; Canteras et al, 1997; Paschoalin-Maurin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%